2011
DOI: 10.1002/anie.201104846
|View full text |Cite
|
Sign up to set email alerts
|

Towards Unimolecular Luminescent Solar Concentrators: Bodipy‐Based Dendritic Energy‐Transfer Cascade with Panchromatic Absorption and Monochromatized Emission

Abstract: Cataloged from PDF version of article.A polymer-embedded dendritic, bodipy-based panchromatic absorber with a built-in energy gradient concentrates incident solar radiation at a terminal chromophore, resulting in a monochromatized emission directed to the sides of the polymer waveguide (see picture). This particular design minimizes self-absorption losses from the peripheral antenna units with an impressive S factor of 10 000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 67 publications
2
133
0
Order By: Relevance
“…3e,10 Recently, in a dendritic light harvester designed for solar concentration, we have experimentally demonstrated that, in such flexible lightharvesting ensembles, simple calculations based on lifetime changes are not applicable. 11 Deviation between energy transfer efficiencies calculated by quantum yield/lifetime changes and calculations based on excitation spectra can be very large. This is due to disregarding any emergent quenching process in the covalent assembly and treating all nonradiative processes involving the donor as energy transfer.…”
mentioning
confidence: 99%
“…3e,10 Recently, in a dendritic light harvester designed for solar concentration, we have experimentally demonstrated that, in such flexible lightharvesting ensembles, simple calculations based on lifetime changes are not applicable. 11 Deviation between energy transfer efficiencies calculated by quantum yield/lifetime changes and calculations based on excitation spectra can be very large. This is due to disregarding any emergent quenching process in the covalent assembly and treating all nonradiative processes involving the donor as energy transfer.…”
mentioning
confidence: 99%
“…The variety of synthetic pathways to BODIPY-based fluorophores allows efficient preparation. The fluorescence properties of BODIPY were tunable by simple substitution at various positions of the difluoroboron dipyrromethene core [25][26][27]. DPA and its derivatives DPEA and TPEA, are well-known receptors for heavy-metal ions [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Alongside stimuli-responsive optics,aparticularly heavily studied topic in contemporary chemistry is Fçrster resonance energy transfer (FRET), the through-space migration of energy from an excited donor to an acceptor molecule that subsequently emits this energy as light. [6,7] FRET plays an important role in energy harvesting systems,f or instance in collecting panchromatic light in an arrow waveband [8] or directing energy to specific reaction centers in the case of photosynthesis. [9] Artificial temperature-responsive FRET systems in supramolecular assemblies have been reported, in which aggregation of the donor and acceptor monomers takes place at lower temperatures resulting in FRET, [10][11][12] while at higher temperatures,e mission is blue-shifted as the thermal disruption of the co-assemblies results in spatial separation of the donor/acceptor pair, causing emission from the donor to be observable.…”
Section: Temperature-responsivel Uminescents Olar Concentrators:t Unimentioning
confidence: 99%